Refining Spectrum Fee to Increase Utilization Efficiency by Adopting ITU-R SM 2012-2 Case Study: Cellular Service in Indonesia - Ismail Ismail; Suhono H. Supangkat; Hendrawan Hendrawan; Basuki Y. Iskandar (Journal of ICT Research and Applications, 2010)
The spectrum fees called as "Biaya Hak Pengguna Frekuensi" (BHPF) for cellular services in Indonesia are currently calculated based on apparatus, proportionally to the number of transceiver stations and radio channels. Unfortunately, the formula cannot promote the efficiency of frequency spectrum efficiency. ITU-R SM 2012-2 recommended the spectrum fee formula that can promote the efficiency; Administrative Incentives Price (AIP) also claims to promote the effectiveness of the radio spectrum utilization. By combining ITUR SM 2012-2 with AIP, the frequency fee formula can promote not only the efficiency but also the effectiveness of spectrum utilization. This paper will explain and discus the modification of ITU-R SM 2012-2 with AIP in designing the spectrum fees for cellular services in Indonesia.